Comparative Analysis Of Oil Palm Farming Patterns Between Plasma And Independent Farmers In North Musirawas Regency - Febrina Nur Annisa; Syabawaihi Syabawaihi (Jurnal Riset Perkebunan, 2023)
This study aims to analyze the influence of partnership types on agricultural outcomes and farmers' income in oil palm plantation enterprises. Data were obtained from 10 farmers divided between plasma and independent partnership types. The observed variables included partnership types, land area, quantity of fertilizer use, herbicide use, and income. Analysis was conducted using descriptive statistical methods, Pearson correlation, paired t-test, and analysis of variance (ANOVA). The results of the study indicate that partnership types significantly affect agricultural outcomes and farmers' income. Plasma farmers tend to have better agricultural outcomes and higher income compared to independent farmers. Additionally, land area and fertilizer use also exhibit significant differences between partnership types. However, herbicide use does not show a significant difference between the two partnership types. In conclusion, partnership types have an impact on agricultural outcomes and farmers' income in oil palm plantation enterprises. These findings hold important implications for policy and strategy development that focuses on enhancing farmers' welfare within the plasma partnership.